Blood Results in Clinical Practice - Basten, Graham (M & K Update Limited, 2019)
This book was originally written after feedback suggested that storytelling was very helpful to students and practitioners wanting to remember blood tests and their implications. Each section, where appropriate, therefore contains a 'story', as well as an overview of the relevant anatomy, physiology and biochemistry. This revised, updated edition continues to use storytelling to aid understanding, and introduces a unique 10-point system to help explain blood results. The use of storytelling has also been significantly improved and refined, following several years of feedback on the first editi.